STRATEGI PEMBERDAYAAN MINA RAHARJA MEALUI INOVASI PRODUK FROZEN FISH FOOD BERBASIS IPTEKS - Dwi Putriana Nuramanah Kinding; Mahardhika Nur Permatasari; Hidrotunnisa Hidrotunnisa; Hani Nazilah; Anik Hidayah (FIP UNIRA MALANG, 2026)
Limited fish processing remains a major challenge in the fisheries sector, leading to low product value addition and restricted market reach due to short shelf life. This condition is also experienced by the Mina Raharja business group in Tayem Village, Cilacap Regency, which primarily focuses on selling fresh fish without further processing. This community service program aims to increase product value and expand market reach through the application of science and technology-based processing innovations. The method employed a participatory approach consisting of socialization, training, mentoring, and follow-up stages involving 15 participants. The training process included raw material preparation, fish cleaning, marination, vacuum packaging, and frozen storage. The results showed that 80% of participants understood the importance of cold chain management and product diversification, while 87% were able to operate vacuum sealers and freezer boxes independently. The resulting products have a shelf life of 4–6 months at −18°C without quality deterioration. This program contributed to improving production capacity, technology adoption, and business management, thereby supporting the transformation from fresh fish sales into value-added processed products.